Strategy of the Hanlon improvement approach to evaluation of the rational use of antibiotics in ARI patients in community health center, Tanjung Jabung Barat district - Aminuddin, Aminuddin; Purwidyanigrum, Ika; Iswandi, Iswandi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Acute respiratory infections is an important public health problem, especially in developing countries. One of the mainstay drugs to overcome this problem is antimicrobials, including antibacterials/antibiotics, antifungals, antivirals,antiprotozoa. Various studies have found that around 40-62% of antibiotics are used inappropriately, including for diseases that do not actually require antibiotics. The aim of this study was to evaluate rational drug use. Method: This research is a non-experimental analytical research withobservationaldesigncross sectional by reviewing the medical records and prescriptions of ISPA patients at the District Health Center. West Tanjung Jabung using the POR method,Drug Related Problems (DRPs) PCNE version 9.1,Gyssen, as well as improvement strategies using the Hanlon method. The research was conducted at Sukarejo Community Health Center and Merlung Community Health Center in April-June 2023 by taking medical record data with a total of 502 medical records which were used to evaluate antibiotics using the POR, PCNE V9.1,I agree, as well as Improvement strategies Hanlon. Results: The results of the study obtained the use of antibiotics at the Sukarejo Health Center of 26% with an average prescription of 3.9 prescriptions, while at the Merlung Health Center of 37% with an average prescription of 3.5, with the right indication 100%, the right type of drug 100%, the right dose 100%, the right way of administration 100%, the right duration of use 0%. From the results of the evaluation of antibiotics at the Sukarejo Health Center and Merlung Health Center, a hanlon improvement strategy was obtained by providing solutions to make SOPs (Standard Operating Procedures) and SPM (Standard Medical Guidelines) so that rational use of antibiotics could occur. Conclusion: The improvement strategy using the Hanlon method is to create Standard Operating Procedures (SOP) and Quality Assurance Standards (SPM) regarding the use of antibiotics and drugs used at Sukarejo Community Health Center and Merlung Community Health Center. And improving Evaluation and Monitoring in Rational Drug Administration. Keywords: POR, PCNE V9.1, Gyssens, Hanlon